Contrastive analysis between the verb ‘hakobu’ in Japanese and the verb ‘membawa’ in Indonesian - Novianti, Annisativa; Judiasri, Melia Dwi; Kusrini, Dewi (Universitas Dian Nuswantoro, 2023)
This study contrasting hakobu verb in Japanese with membawa verb in Indonesian. Hakobu verb if translated into Indonesian can be interpreted as 'membawa'. However, hakobu verb does not always have the meaning ‘membawa’ when translated into Indonesian. This can cause errors when translating hakobu verb into Indonesian or vice versa. The purpose of this study is to find out the similarities and differences between hakobu verb in Japanese with membawa verb in Indonesian in order to anticipate errors in Japanese learners. The method used is descriptive contrastive analysis method in which data in the form of sentences are obtained from websites and e-books totaling 37 sentences. Based on the data analysis it can be concluded that there are 3 similarities and 2 differences between hakobu verb and membawa verb. The similarity between hakobu verb with membawa verb is both having the meaning of (1) transport, move using tools; (2) holding, lifting while walking; (3) putting on something while moving. While the difference between the hakobu verb with membawa verb is hakobu verb has the meaning of (1) to carry out, to do; (2) making progress, in progress, ongoing but membawa verb doesn't have that meaning. Another difference is membawa verb has the meaning of (1) invite out, to go together; (2) to bring about, to cause; (3) pull, involve, while hakobu verb doesn't have that meaning. The results of this study can provide input for Japanese language teaching in the future.